2017
DOI: 10.4062/biomolther.2017.074
|View full text |Cite
|
Sign up to set email alerts
|

α, γ-Mangostins Induce Autophagy and Show Synergistic Effect with Gemcitabine in Pancreatic Cancer Cell Lines

Abstract: Pancreatic cancer is one of the most lethal and aggressive cancers in the world. However, no effective treatment is currently available for pancreatic cancer. The objective of this study was to determine the anti-pancreatic cancer effect of α-mangostin (αM) and γ-mangostin (γM) extracted from the pericarp of Garcinia mangostana L.. Both αM and γM reduced the viability of pancreatic cancer cells MIA PaCa-2 and PANC-1 in a dose-dependent manner. These compounds induced apoptosis by increasing c-PARP and c-Caspas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…As shown in Figure 1A,B, MA repressed the growth of GBC cells in a time-and dose-dependent manner. The half-maximum inhibitory concentrations of MA were approximately 5 μmol/L in the NOZ and GBC-SD cells, which were similar to previous results and did not have cytotoxic effects in normal bile duct epithelial cell lines (HIBEC, as shown in Figure S1) 21 ; thus, we selected 5 μmol/L MA for the subsequent experiments. To interrogate the effects of MA on the proliferation of GBC cells, NOZ and GBC-SD cells were treated with 5 μmol/L MA to evaluate colony formation.…”
Section: α-Mangostin Suppresses Proliferation and Induces Apoptosissupporting
confidence: 83%
See 1 more Smart Citation
“…As shown in Figure 1A,B, MA repressed the growth of GBC cells in a time-and dose-dependent manner. The half-maximum inhibitory concentrations of MA were approximately 5 μmol/L in the NOZ and GBC-SD cells, which were similar to previous results and did not have cytotoxic effects in normal bile duct epithelial cell lines (HIBEC, as shown in Figure S1) 21 ; thus, we selected 5 μmol/L MA for the subsequent experiments. To interrogate the effects of MA on the proliferation of GBC cells, NOZ and GBC-SD cells were treated with 5 μmol/L MA to evaluate colony formation.…”
Section: α-Mangostin Suppresses Proliferation and Induces Apoptosissupporting
confidence: 83%
“…21,22 In addition, α-mangostin kills cancer cells by inducing cell cycle arrest, apoptosis and autophagic cell death; moreover, α-mangostin suppresses oxidation, invasion and metastasis of several types of cancer. 21 However, the molecular mechanisms of the effects of α-mangostin in GBC cells have not yet been reported. Interestingly, α-mangostin triggers the autophagy-related cell death of glioblastoma cells by activating AMPK (AMP-activated protein kinase).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, biofabricated silver nanoparticle containing water extract of mangosteen bark was reported to preferentially killed A549 lung cancer cells (Zhang & Xiao, 2018). In addition, Kim, Chin & Lee (2017) showed that the mixture of α- and γ-mangostin can inhibit pancreatic cancer cell lines. Their action were contributed by possible autophagy development via AMP-activated protein kinase/mTOR and p38 pathways (Kim, Chin & Lee, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Kim, Chin & Lee (2017) showed that the mixture of α- and γ-mangostin can inhibit pancreatic cancer cell lines. Their action were contributed by possible autophagy development via AMP-activated protein kinase/mTOR and p38 pathways (Kim, Chin & Lee, 2017). Interestingly, both compounds, together with a common drug called gemcitabine, were also found to synergistically inhibit the cancer cells (Kim, Chin & Lee, 2017), highlighting possible drug concoction for better treatment efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…9 Previous studies have demonstrated that α-M has a number of biological activities, including antibacterial, 10 cardioprotective, 11 neuroprotective, 12 and anticancer effects. 13,14 The antitumor effects of α-M regulate the proliferation and apoptosis of GC cells and have been implicated in diverse activities, including modulation of autophagy. 15 However, the molecular mechanism of α-M in autophagy and chemotherapeutic drug resistance in GC cells have not been fully elucidated.…”
mentioning
confidence: 99%